Genetic Control of Aerogel and Nanofoam Properties, Applied to Ni–MnOx Cathode Design. (23rd June 2021) - Cha, Tae‐Gon; Tsedev, Uyanga; Ransil, Alan; Embree, Amanda; Gordon, D. Benjamin; Belcher, Angela M.; Voigt, Christopher A.
Abstract: Aerogels are ultralight porous materials whose matrix structure can be formed by interlinking 880 nm long M13 phage particles. In theory, changing the phage properties would alter the aerogel matrix, but attempting this using the current production system leads to heterogeneous lengths. A phagemid system that yields a narrow length distribution that can be tuned in 0.3 nm increments from 50 to 2500 nm is designed and, independently, the persistence length varies from 14 to 68 nm by mutating the coat protein. A robotic workflow that automates each step from DNA construction to aerogel synthesis is used to build 1200 aerogels. This is applied to compare Ni–MnO x cathodes built using different matrixes, revealing a pareto‐optimal relationship between performance metrics. This work demonstrates the application of genetic engineering to create "tuning knobs" to sweep through material parameter space; in this case, toward creating a physically strong and high‐capacity battery. Abstract : An engineered phagemid system generates M13 phage with tunable length and stiffness. Changing the phage properties changes the electrochemical and mechanical properties of metal nanofoams, used as cathodes in Li ion batteries. This is applied to scan the properties of cathodes to identify those with high capacity and strength, as a step towards structural batteries.